SASTRA ANAK SEBAGAI AWAL PENDIDIKAN KARAKTER DALAM CERPEN SERI “AKU MAU MENDENGARKAN”, “AKU BERANI BERTERIMAKASIH”, DAN “AKU MAU MEMAAFKAN” KARYA ADE YULIA - Nur Innayah Ganjarjati (Khazanah Pendidikan, 2019)
ABSTRACTThis research is about how literature, especially children’s literature canbe a character building for children. In literary works, the author has the purposeconveyed, moral, religious and political goals. To find out the objectives to beconveyed by the author, can be analyzed through pragmatics. In the series ofshort story entitled "Aku Mau Memaafkan ",”Aku Berani Berterimakasih” and" Aku Mau Memaafkan " by Ade Yulia, the author discusses more about moralgoals / messages. is our learning to educate someone at the request given, learnto apologize and forgive the mistakes we make and encourage thanks for the helpthat others have given us. From good behavior, words and habits it will producegood morality and character also, because relating to literary works, especiallychildren's literature can be the beginning of children's character building.Keywords: Children's Literature, Character Building, Short Story.